2020
DOI: 10.1039/d0fo02158j
|View full text |Cite
|
Sign up to set email alerts
|

Hydroalcoholic extract fromAbelmoschus manihot(Linn.) Medicus flower reverses sleep deprivation-evoked learning and memory deficit

Abstract: Extract of Abelmoschus manihot flower (EAM) has the potential to ameliorate learning and memory deficit, in part through inhibiting oxidative stress in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Acute SD induces oxidative stress and subsequent memory impairments (Aleisa et al, 2011[ 2 ]). A previous research has shown that SD impairs object location recognition and passive avoidance memories via increasing oxidative stress in the brain (Zhou et al, 2020[ 129 ]). It has also been revealed that 5-day TSD induces spatial memory decline in the Morris water maze task through increasing oxidative stress in the hippocampus of rats (Wang et al, 2018[ 119 ]).…”
Section: The Mechanisms Underlying the Effects Of Sd On Learning And Memorymentioning
confidence: 99%
“…Acute SD induces oxidative stress and subsequent memory impairments (Aleisa et al, 2011[ 2 ]). A previous research has shown that SD impairs object location recognition and passive avoidance memories via increasing oxidative stress in the brain (Zhou et al, 2020[ 129 ]). It has also been revealed that 5-day TSD induces spatial memory decline in the Morris water maze task through increasing oxidative stress in the hippocampus of rats (Wang et al, 2018[ 119 ]).…”
Section: The Mechanisms Underlying the Effects Of Sd On Learning And Memorymentioning
confidence: 99%